Silver(I) complexes with symmetrical Schiff bases: Synthesis, structural characterization, DFT studies and antimycobacterial assays - Paiva, Isabela L.; De Carvalho, Gustavo S.G.; Da Silva, Adilson D.; Corbi, Pedro P.; Bergamini, Fernando R.G.; Formiga, André L.B.; Diniz, Renata; Do Carmo, Weberton R.; Leite, Clarice Q.F. [UNESP]; Pavan, Fernando Rogério [UNESP]; Cuin, Alexandre (Elsevier, 2013)
Synthesis, structural and spectroscopic characterizations, molecular modeling and antimycobacterial assays of new silver(I) complexes with two Schiff bases - MBDA and MBDB - are reported. The complexes [Ag(MBDA) 2]NO3, or AgMBDA, and [Ag(MBDB)NO3] or AgMBDB, were obtained by the reaction of the respective ligands with silver(I) nitrate in methanol. The Schiff bases were previously obtained by mixing ethylenediamine or 1,3-diaminopropane with p-anisaldehyde. The characterizations of the complexes were based on elemental (C, H and N) and thermal (TG-DTA) analyses and 13C and 1H NMR and FT-IR spectroscopic measurements, as well as X-ray structure determination for AgMBDA. Spectroscopic data predicted by DFT calculations are in agreement with the experimental data for the AgMBDA complex. The AgMBDA complex has a monomeric structure with a molar proportion 1:2 Ag/ligand, while AgMBDB presents a 1:1 proportion. The complexes AgMBDA and AgMBDB showed to be more effective against Mycobacterium tuberculosis than antibacterial agent silver sulfadiazine - SSD. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Anisaldehyde; Mycobacterium; Schiff bases; Silver; Tuberculosis